Providing technical assistance: lessons learned from the first three years of the WHO Adolescent and Youth Sexual and Reproductive Health and Rights Technical Assistance Coordination Mechanism - Bruce Dick; Marina Plesons; Callie Simon; Jane Ferguson; Ahmed Kassem Ali; Venkatraman Chandra-Mouli (BMC, 2024)
Abstract Young people's sexual and reproductive health (SRH) continues to be a major challenge in low and middle-income countries, with implications for public health now and in the future. Fortunately there is a growing array of evidence-based interventions, and commitments from governments, development partners and donors, to support programmes that aim to improve young people's SRH. However, in some situations, the technical assistance that governments feel that they need to strengthen and implement national policies and strategies, to move from words to action, is not available. The WHO Adolescent and Youth Sexual and Reproductive Health and Rights (AYSRHR) Technical Assistance (TA) Coordination Mechanism was initiated to help fill this technical assistance gap; to respond to TA requests from ministries of health in ways that are timely, efficient, effective and contribute to strengthening capacity. This paper describes the process of developing the Technical Assistance Coordination Mechanism (TA Mechanism) and the outcomes, experiences and lessons learned after three years of working. It triangulates the findings from a preliminary review of the literature and discussions with selected key informants; the outcomes from a series of structured review meetings; and the documented processes and results of the technical assistance provided to countries. The lessons learned focus on three aspects of the TA Mechanism. How it was conceptualized and designed: through listening to people who provide and receive AYSRHR TA and by reviewing and synthesizing past experiences of TA provision. What the TA Mechanism has achieved: a standardized process for TA provision, at different stages for a range of AYSRHR issues in ten countries in three geographic regions. And what worked well and what did not: which common challenges was the TA Mechanism able to address and which ones persisted despite efforts to avoid or resolve them. The paper ends with the implications of the lessons learned for future action.